Peran Gaya Kepemimpinan dan Budaya Organisasi dalam Meningkatkan Kinerja Karyawan Melalui Kepuasan Kerja di Bank Sulutgo - Prasetyo, Iman; Ali, Hapzi; Rekarti, Endi (Dinasti Review, 2023)
Employee performance problems that occur at Bank Sulutgo are caused by various factors, including leadership style, poor organizational culture, and low job satisfaction which is characterized by suboptimal performance, so this research aims to analyze the influence of leadership style and organizational culture in improving employee performance through job satisfaction at Bank Sulutgo. The research method uses Structural Equation Modeling (SEM) Smart PLS. The results of the research show that leadership style and work culture directly influence job satisfaction, leadership style does not influence performance, work culture and job satisfaction influence the performance of Bank Sulutgo employees. Indirectly, job satisfaction mediates the influence of leadership style and organizational culture on the performance of Bank Sulutgo employees. It is necessary to pay attention to the factors that most influence employee performance, including leaders mingling with employees within the company, maintaining the organizational culture condition remains stable, and maintaining a comfortable and safe environment for employees, so that employees can carry out their duties well and effectively achieve company goals. In addition, there is a need to increase emphasis from leaders on subordinates to be task-oriented so that employee performance can be better.